Intracontinental Fault Reactivation in High Heat Production Areas of Central Australia: Insights From Apatite Fission Track Thermochronology. (11th December 2022) - Nixon, A. L.; Glorie, S.; Fernie, N.; Hand, M.; De Vries Van Leeuwen, A. T.; Collins, A. S.; Hasterok, D.; Fraser, G.
Abstract: Pervasive intracontinental orogenesis during the Paleozoic has been widely recognized in the metamorphic and structural records of the Aileron Province and Amadeus Basin in central Australia, commonly attributed to the Ordovician–Carboniferous Alice Springs Orogeny. Comparatively less clear, however, is the magnitude and geographic expression of this event elsewhere in the North Australian Craton. This study presents new apatite fission track thermochronology data from central Australia which demonstrate considerable Paleozoic reactivation across the continental interior. Both the Tennant region and Murphy Province exhibit low‐temperature cooling coeval with the Alice Springs Orogeny (ca. 450–320 Ma), although Triassic reactivation in the Aileron Province correlates with the timing of the Hunter‐Bowen Orogeny (ca. 265–230 Ma) in eastern Australia. High heat production and metasomatism within the Aileron Province has made the region highly susceptible to reactivation, rendering it more vulnerable to subsequent reactivation in response to far‐field stresses during the progressive Tasmanides development. Plain Language Summary: It is well known that deformation such as bending and breaking of rocks is focused near boundaries of tectonic plates as they collide with one another. For the last billion years central Australia has been located far from the edges of these plates, yet similar deformation has been found in this region as would be expected close to the plate boundaries. Evidence suggests deformation occurred across much of central Australia at around 400 million years ago, although more local deformation occurred at around 230 million years ago. More recent, localized deformation is only seen in regions which the shallow Earth is unusually hot due to the presence of radioactive elements which make the rocks weaker and easier to break. In both cases, this deformation represents movement and erosion in the upper 3 km of the Earth, likely caused as stresses from the plate boundaries pushed far inland as the Pacific Plate collided with the Australian Plate at this time in eastern Australia. This suggests a much larger geographical impact of this collision, and means we can now predict deformation far inland during this time in addition to the areas close to the plate boundaries where it would be conventionally expected. Key Points: Basement fault reactivation during Alice Springs Orogeny is pervasive throughout central Australia Brittle, shallow crustal deformation dominates central Australia away from the high heat producing central Aileron Province Deformation coinciding with the youngest Tamanide orogens is preserved in the Aileron Province due to thermal weakening